2003
DOI: 10.1021/ic034559m
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Energy-Transfer Dynamics in Self-Assembled Triads Composed of Two Porphyrins and an Intervening Bis(dipyrrinato)metal Complex

Abstract: The synthesis and characterization of various triads composed of a linear array of two zinc porphyrins joined via an intervening bis(dipyrrinato)metal(II) complex are reported. The preparation exploits the facile complexation of dipyrrins with divalent metal ions to give bis(dipyrrinato)metal(II) complexes [abbreviated (dp)(2)M]. Copper(II) and palladium(II) chelates of dipyrrins (available by oxidation of dipyrromethanes) were prepared in 50-80% yield. A one-flask synthesis of bis(dipyrrinato)zinc(II) complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
211
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(222 citation statements)
references
References 93 publications
(155 reference statements)
6
211
0
5
Order By: Relevance
“…With regard to coordinating ligands, dipyrrins (dipyrromethenes), as partial structures of bile pigments consisting of two pyrroles with an sp 2 meso position, are essential π-conjugated bidentate monoanionic ligands for metal ions in natural and artificial systems. [11][12][13] Multitopic dipyrrin derivatives are promising scaffolds for self-assemblies and would provide neutral coordination oligomers, which, in combination with various spacer units, could be used to fabricate supramolecular structures and fine-tuned nanoscale morphologies by means of bridging metal cations. For example, Cohen et al showed infinite coordination networks based on dipyrrin derivatives in the solid state (Figure 2a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to coordinating ligands, dipyrrins (dipyrromethenes), as partial structures of bile pigments consisting of two pyrroles with an sp 2 meso position, are essential π-conjugated bidentate monoanionic ligands for metal ions in natural and artificial systems. [11][12][13] Multitopic dipyrrin derivatives are promising scaffolds for self-assemblies and would provide neutral coordination oligomers, which, in combination with various spacer units, could be used to fabricate supramolecular structures and fine-tuned nanoscale morphologies by means of bridging metal cations. For example, Cohen et al showed infinite coordination networks based on dipyrrin derivatives in the solid state (Figure 2a).…”
Section: Introductionmentioning
confidence: 99%
“…[12] Lindsey et al reported dipyrrin metal complexes as bridging units for energy transfer systems consisting of porphyrins (Figure 2b). [13] Apart from these studies, the author has also attempted to form coordination oligomers to yield nanoscale spherical architectures and discrete coordination macrocycles by using dimeric dipyrrin derivatives. [14][15][16] In natural systems, the double helix of DNA is constructed by complementary hydrogen-bonding between the base pairs, and the high-dimensional structures of proteins are maintained by means of noncovalent interactions between subunits such as amides.…”
Section: Introductionmentioning
confidence: 99%
“…Many photosynthetic light harvesting systems are arranged as noncovalent molecular assemblies, with the degree of systematic order in the ensembles varying widely (Logunov and Rodgers 1992;Fujihira 1993;Cox 1997;Chen et al 2002;Yu et al 2003). While there are a large number of self-assembling synthetic light harvesting systems, there are also many artificial systems that involve covalently linked arrays of chromophores that can be isolated and fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…[6,9] Moreover, Bocian, Holten, Lindsey et al have exploited the (dpy)-Zn-(dpy) linkage to create bisporphyrinbased energy-transfer systems. [10] However, to the best of our knowledge bridging bis(dipyrrinato)zinc motifs have not been used as linking moieties to produce charge-separating devices. Complex 1 was designed to test this potential utility.…”
mentioning
confidence: 99%